Efektivitas Metode Dakwah Bil Hikmah Dalam Penyebaran Islam Di Desa Kuta Gerat Kec.Munthe Kab.Karo - Dwiva Ramadani Ginting; Muhammad Fadhli Pulungan; Fadlan Habib; Sarhul Azkar Pohan; Mansyursyah; Rusydi Aulia Siregar (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
This study aims to explore the effectiveness of the method of dakwah bil hikmah in spreading Islam in Kuta Gerat Village, Munthe District, Karo Regency. The dakwah bil hikmah method is an approach to dakwah that emphasizes wisdom, gentleness, and softness in conveying the teachings of Islam to the community. This research uses a qualitative approach with data collection techniques through participatory observation, interviews, and documentary studies. The results of the study indicate that the dakwah bil hikmah method is effective in spreading Islam in Kuta Gerat Village, with the community responding positively to the persuasive approach and emphasis on dialogue. Additionally, this method helps strengthen ukhuwah Islamiyah and broaden the understanding of religion among the community. The implications of this study underscore the importance of considering a wise and gentle approach to dakwah in efforts to spread Islam in diverse community settings.